Pengaruh Kompetensi Sumber Daya Manusia Terhadap Efektivitas Penyusunan Anggaran Perusahaan - Devi Indah Sari; Sunarto (Indo-MathEdu Intellectuals Journal, 2026)
The effectiveness of a company's budgeting is significantly influenced by the competence of the human resources involved in the budget planning and management process. This study aims to analyze the influence of human resource competence on the effectiveness of a company's budgeting. The study used a quantitative approach with an associative method. The study population consisted of employees involved in the budgeting process, such as those in finance, accounting, planning, budget administration, and work unit managers. Data were collected through questionnaires and analyzed using simple linear regression. Human resource competence was measured through indicators of financial knowledge, technical skills, analytical ability, work experience, mastery of information technology, communication, and integrity, while budgeting effectiveness was measured based on planning accuracy, budget quality, and budget target achievement. The results showed that human resource competence had a positive and significant effect on the effectiveness of a company's budgeting. This finding indicates that improving employee competence can support more accurate, effective, and aligned budgeting in line with organizational goals. Therefore, developing human resource competence needs to be a primary concern for companies in efforts to improve the quality of budget management.